MODERN TRENDS OF DEVELOPMENT OF THE CONSULTING SERVICES MARKET - V. Zhukov (Вестник университета)
In the article the stages of the functioning of the consulting services market are analyzed, the criteria for classifying the entire spectrum of consulting companies are determined and the features of the activity of each selected type of organization are investigated. The segmentation of consumers of consulting services was done. The associations of consultants and consulting agencies and their functions are considered. The tendencies of development of the world market of consulting services are revealed: attraction of various consultants; fight for qualified personnel; introduction of modern information technologies; orientation on the healthcare industry; formation of new models of counseling.